Zawartość i dystrybucja fosforu oraz aktywność fosfataz w leśnych glebach rdzawych w obszarze długoletniego oddziaływania Zakładów Azotowych Anwil we Włocławku - Lemanowicz, Joanna (Leśne Prace Badawcze, 2015)
This paper presents the results of research examining the soil content of total and available phosphorus (P E-R ) taking the activity of alkaline and acid phosphatase into consideration. For this study three soil profiles were sampled in Arenosols at a distance of 0.8 km, 2.0 km and 2.5 km from the Nitrogen Works Anwil SA as well as a control profile in the Tuchola Forest. The soils’ reaction ranged from acidic to very acidic. The humus content in the surface horizons of the sampled profiles was average (1.26 – 2.61%). The lowest P E-R content was found in the profile sampled closest (0.8 km) to the Nitrogen Works. The Distribution Index (DI) calculated for available phosphorus pointed towards moderate accumulation, while at the same time the availability index (IM) confirmed low availability especially in profile I. The activity of alkaline and acid phosphatase, which are the enzymes responsible for the phosphorus transformation in the soil, varied depending on the distance from the Nitrogen Works. Inhibition of alkaline phosphomonoesterases and stimulation of the acid esterases, which were both connected to the examined soil reaction, were observed. The activity of phosphatases as well as total and available phosphorus content were decreasing steeply along the soil profiles. Furthermore, a significant correlation between Corg and the activity of alkaline and acid phosphatase ( r= 0.94, p< 0.05 and r= 0.67, p< 0.05, respectively) as well as between the content of P E-R and the activity of alkaline phosphatase ( r= 0.67, p< 0.05) was recorded. The results suggest a need for further research and monitoring of Arenosols in the forest affected by the Nitrogen Works.